A study of serum electrolytes level in viral hepatitis E patients in a tertiary care hospital of south Gujarat - Shah, Ravi; Shah, Parshv; Shah, Hemant; Doctor, Nilesh (International Journal of Advances in Medicine, 2021)
Background: the aim of the study was to find and understand the relation between electrolytes and viral hepatitis E. To study electrolyte abnormality in patients with hepatitis E virus (HEV). Methods: This study is a single centre cross sectional study on the patients with HEV infection. Consecutive cases affected with HEV-at department of medicine, SMIMER (Surat Municipal institute of medical education and research) hospital, Surat during the period of 1 year (July-2019 to June-2020) are taken up for the study. Results: Abnormal electrolytes are associated with higher mortality in patients infected with HEV. Conclusions: A higher mean serum creatinine, total bilirubin, SGOT, SGPT; lower total protein, albumin, and abnormal electrolytes in body fluid (Na+, K+, Cl-, Ca++) values are associated with higher mortality in patients infected with HEV.